The pet trade of native species outside of their natural distributions within Australia is a biosecurity risk - Adam Toomes; Oliver C. Stringham; Stephanie Moncayo; Katherine G. W. Hill; Jacob Maher; Freyja Watters; Sebastian Chekunov; Pablo García‐Díaz; Lewis Mitchell; Joshua V. Ross; Phillip Cassey (Conservation Science and Practice)
Abstract The trade of alien species as pets is increasingly recognized as a biosecurity risk due to their intentional and accidental release into the wild. However, pets are often categorized as native or non‐native at a national level, meaning that their presence outside of their native range, yet within their native country, may be an overlooked biosecurity threat. So‐called “domestic non‐natives” have established new populations across several countries and, in some cases, become invasive. Here, we investigated the extent of the domestic trade of native Australian pet species outside of their natural distributions and determined whether such locations were climatically suitable for potential alien establishments. Australia provides a unique system to explore this issue because it deters the trade of most alien species yet permits the keeping of a large diversity of native pets. We monitored trade from a popular Australian e‐commerce site used to trade native pet birds, reptiles, and amphibians (29 k advertisements over 1 year; from July 2019 to July 2020). Of the 177 native vertebrate species we observed in the pet trade, 129 species (73%) had at least some instances of their trade occurring outside of their natural distribution. We found that climatically suitable environments were present outside the native range of 90 species and that these regions were proximal to suburbs where we observed trade. Our results indicate that the “domestic non‐native” trade is widespread in Australia and that, if captive pets escape or are released into the wild in sufficient numbers, there is a risk of establishment for most of these species. We suggest that regulations pertaining to the trade of native pets ensure that careful biosecurity consideration is given in circumstances when trade occurs beyond a species' native range, both in the context of Australia and for other large countries with widespread pet industries.